(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: AKI is a consequential complication seen in critically ill patients, causing severe morbidity and mortality. Conventional biomarkers, such as serum creatinine and urine output, have limited sensitivity and specificity for detecting early kidney damage. The identification of novel biomarkers enables earlier and more accurate detection of AKI for improving prognosis. Methods: A comprehensive literature review using the PICO framework (Population: critically ill patients; Intervention; novel biomarkers; Comparison: traditional biomarkers; Outcome: early detection of AKI with biomarkers of more sensitivity and specificity) was conducted. The literature review was performed by searching studies in PubMed, Google Scholar, Embase, and Scopus, conducted between 2010 and 2024 using relevant keywords. Two reviewers were involved in screening articles, data extraction, and assessment of study quality using different bias tools. Results: A total of 37 articles were retrieved to evaluate biomarkers such as neutrophil gelatinase-associated lipocalin (NGAL), kidney injury molecule-1 (KIM-1), interleukin-18 (IL-18), liver-type fatty acid-binding protein (L-FABP), serum cystatin C and tissue inhibitor of metalloproteinases-2 and insulin-like growth factor-binding protein 7 (TIMP-2·IGFBP7). Significant heterogeneity was observed among studies, but overall trends supported the utility of these biomarkers in early AKI detection. Conclusion: NGAL, KIM-1, and TIMP-2·IGFBP7 helps in earlier diagnosis of Acute Kidney Injury in acutely ill patients leading to appropriate interventions along with improved consequences. However, large-scale studies are needed to integrate these biomarkers in our daily clinical practice.